Kinky desires: Why there is no Moore’s Paradox of Desire - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2008)
G.E. Moore famously observed that to say, ‘I went to the pictures last Tuesday but I don’t believe that I did’ or ‘I believe that he has gone out, but he has not’ (1944, 204). would be ‘absurd’. Moore-paradoxical omissive or commissive beliefs of the forms p & I do not believe that p and p & I believe that not-p. are also absurd, although their contents are possible truths. Can there be ‘Moorean desires’, namely desires of the forms I desire both that (p & I do not desire that p) and I desire both that (p & I desire that not-p) that are ‘Moore-paradoxical’, in the sense that they are absurd roughly in the way Moore-paradoxical beliefs are absurd? I argue that the most promising approach to a yes is a normative account of doxastic Moore-paradoxicality that parallels a normative account of Moorean desire. It turns out that this won’t work, not because there are no norms of desire, but because the norms required are ones we should reject. Unlike Moorean belief, which is always irrational, Moorean desire, although often odd, is sometimes sensible. An interesting lesson to be learned along the way—and an important one for functionalism—is that the logic of desire differs from that of both conscious belief and belief per se.